Analysis of dietary patterns and cross-sectional and longitudinal associations with hypertension, high BMI and type 2 diabetes in Peru. Issue 6 (28th April 2020) - Alae-Carew, Carmelia; Scheelbeek, Pauline; Carrillo-Larco, Rodrigo M; Bernabé-Ortiz, Antonio; Checkley, William; Miranda, J Jaime
Abstract: Objective: To determine if specific dietary patterns are associated with risk of hypertension, type 2 diabetes mellitus (T2DM) and high BMI in four sites in Peru. Design: We analysed dietary patterns from a cohort of Peruvian adults in four geographical settings using latent class analysis. Associations with prevalence and incidence of hypertension, T2DM and high BMI were assessed using Poisson regression and generalised linear models, adjusted for potential confounders. Setting: Four sites in Peru varying in degree of urbanisation. Participants: Adults aged ≥35 years ( n 3280). Results: We identified four distinct dietary patterns corresponding to different stages of the Peruvian nutrition transition, reflected by the foods frequently consumed in each pattern. Participants consuming the 'stage 3' diet, characterised by high proportional consumption of processed foods, animal products and low consumption of vegetables, mostly consumed in the semi-urban setting, showed the highest prevalence of all health outcomes (hypertension 32·1 %; T2DM 10·7 %; high BMI 75·1 %). Those with a more traditional 'stage 1' diet characterised by potato and vegetables, mostly consumed in the rural setting, had lower prevalence of hypertension (prevalence ratio; 95 CI: 0·57; 0·43, 0·75), T2DM (0·36; 0·16, 0·86) and high BMI (0·55; 0·48, 0·63) compared with the 'stage 3' diet. Incidence of hypertension was highest among individuals consuming the 'stage 3' diet (63·75 per 1000 person-years; 95 % CI 52·40, 77·55). Conclusions: The study found more traditional diets were associated with a lower prevalence of three common chronic diseases, while prevalence of these diseases was higher with a diet high in processed foods and low in vegetables.